INTERNATIONAL COPYRIGHT TREATIES AND ITS IMPLEMENTATION UNDER INDONESIAN COPYRIGHT ACT; IS IT A BETTER ACCESS TO KNOWLEDGE? - Barizah, Nurul (Indonesian Journal of International Law, 2016)
The Indonesian Government has enacted a new Copyright Act in 2014 on the basis that Copyright protection plays a strategic role for economic development and people’s prosperity. This new Act provides a higher standard of protection and ensures more legal certainty to copyrights holders. It is not only expands the scope of protection, duration, but also provides better economic rights to the right holder. This Article analyses Indonesia’s obligation under international treaties and whether Indonesia takes full advantages of all the flexibilities available under those treaties to enhance access to knowledge particularly for educational materials. It also analyses substantial provisions of the new Copyright Act in the context of scope, duration, limitations, and its exceptions. This Article argues that strongest protection of copyright is far beyond what is required by the international copyright treaties which Indonesia has acceded to them. This Article also argues that all available limitations and exceptions provided by the treaties that would have opened up access to knowledge has not all incorporated into the new Act. Accordingly, this Act has a potential to inhibit access to knowledge.